A case of ultrashort‐acting beta‐blocker landiolol hydrochloride for takotsubo syndrome with left ventricular outflow tract obstruction. (7th December 2018) - Takama, Takuro; Fukue, Mitsunori; Sato, Hiroyuki; Taniuchi, Masato
Abstract: Takotsubo syndrome (TTS) has been known to have a favorable prognosis. Beta‐blockers are reported to be effective for TTS patients with cardiogenic heart failure due to left ventricular outflow tract (LVOT) obstruction. However, there is no report on ultrashort‐acting beta‐blockers being used for treating TTS, and there are no clear guidelines for their dosages or applications. Herein, we describe a 72‐year‐old woman in whom landiolol hydrochloride was used in the acute phase of TTS with LVOT obstruction. In this case, the dose of landiolol hydrochloride was increased to 10 μg/kg/min, resulting in improvement of LVOT obstruction, which led to hemodynamic stabilization. Abstract : The LVG findings, in diastole and systole, reveal apical ballooning and hyperdynamic contraction of basal segments.